Determination of the Dynamic Properties of SDOF and MDOF Shear Frames with Image Processing Technique - Çağla Şekerci; Erdem Damcı (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
In this study, experimental modal analyses on shear frame models consisting of single and multi-degree-of-freedom structure models were carried out to examine structural behavior. The image processing technique is used for the tests on shaking tables, such as free vibration, simple harmonic, and strong ground motion. An approach is proposed for image processing techniques to consider the appropriate filter size. The experiments aimed to determine the displacements at the floor levels and the dynamic characteristics of the structure models. To determine the displacements and frequency responses, results obtained from three different methods, namely the data obtained by accelerometers, image processing technique, and theoretical calculations, were compared. It has been shown that the image processing technique is a good tool compared to frequently used vibration measurements with accelerometers. It is advantageous because it is easier to implement for laboratory experiments and less costly.